2014
DOI: 10.1039/c3ra47932c
|View full text |Cite
|
Sign up to set email alerts
|

Facile hydrothermal synthesis and electrochemical properties of orthorhombic LiMnO2cathode materials for rechargeable lithium batteries

Abstract: Pure-phase and aluminum-doped orthorhombic LiMnO2 (o-LiMnO2) samples of high discharge capacity and cyclic stability are prepared by a simple one-step hydrothermal reaction with low Li/Mn molar ratio. Mixing LiMn2O4 and doping aluminum improve the electrochemical performance of o-LiMnO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Until recently, carbon and carbon based materials, [9][10][11][12][13] metal oxides, [14][15][16][17] nitrides, 18,19 carbides, [20][21][22][23] and their composites [24][25][26][27] have been employed as anode materials for LIBs. With respect to cathode materials, Almost all the research and commercialization has centered on the layered compounds with an anion close-packed or almost close-packed lattice like LiCoO 2 , 28,29 LiMnO 2 , 30,31 and transition-metal phosphates, such as olivine LiFePO 4 . 32,33 In SCs, carbonaceous materials, conducting polymers, metal oxides and composites of these aforementioned materials are the common electrode materials that have been employed extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, carbon and carbon based materials, [9][10][11][12][13] metal oxides, [14][15][16][17] nitrides, 18,19 carbides, [20][21][22][23] and their composites [24][25][26][27] have been employed as anode materials for LIBs. With respect to cathode materials, Almost all the research and commercialization has centered on the layered compounds with an anion close-packed or almost close-packed lattice like LiCoO 2 , 28,29 LiMnO 2 , 30,31 and transition-metal phosphates, such as olivine LiFePO 4 . 32,33 In SCs, carbonaceous materials, conducting polymers, metal oxides and composites of these aforementioned materials are the common electrode materials that have been employed extensively.…”
Section: Introductionmentioning
confidence: 99%
“…During cycling, the capacity contribution in the 4 V region increases, resulting in an increase in the overall capacity. After 5 cycles, the cathode could deliver a capacity of 265 mAh g -1 , which is higher than those reported in the literature [20,[32][33][34][35][36][37]. The dQ/dV plot (Figure 4(b)) shows peaks that correspond to the plateaus observed in Figure 4(a).…”
Section: Resultsmentioning
confidence: 58%
“…However, too much lithium source was used and the electrochemical performance of the obtained product was not investigated. In addition, Chen et al [20] have reported that the pure-phase LiMnO 2 with good electrochemical performance were prepared by one-step hydrothermal reaction of MnCl 2 , EDTA, LiOH, and NaClO solutions. It's important to note, however, that the preparation procedure needs additional complexant EDTA and the raw material NaClO is very corrosive, which may do harm to our body.…”
Section: Introductionmentioning
confidence: 99%